Cardiopulmonary Bypass and Oxidative Stress - Zakkar, Mustafa (Oxid Med Cell Longev, 2015)
The development of the cardiopulmonary bypass (CPB) revolutionized cardiac surgery and contributed immensely to improved patients outcomes. CPB is associated with the activation of different coagulation, proinflammatory, survival cascades and altered redox state. Haemolysis, ischaemia, and perfusion injury and neutrophils activation during CPB play a pivotal role in oxidative stress and the associated activation of proinflammatory and proapoptotic signalling pathways which can affect the function and recovery of multiple organs such as the myocardium, lungs, and kidneys and influence clinical outcomes. The administration of agents with antioxidant properties during surgery either intravenously or in the cardioplegia solution may reduce ROS burst and oxidative stress during CPB. Alternatively, the use of modified circuits such as minibypass can modify both proinflammatory responses and oxidative stress.